Either "Hello" or "Wei" seeing Chinese culture in advertisements - Zhang, Wenru (2008)
Advertising is viewed as a cultural artifact and reflects a way of life, as well as social values and cultural beliefs. Therefore, advertising in China may be characterized as a window to the dynamic, ever-changing Chinese society. This study focuses on a single product, the mobile phone and identifies changes in cultural values.